2005
DOI: 10.1159/000084277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucagon-Like Peptide-1(7–36) and Exendin-4 on the Vascular Reactivity in Streptozotocin/Nicotinamide-Induced Diabetic Rats

Abstract: We investigated the vascular effects of glucagon-like peptide-1 (GLP-1) and Exendin-4 in type 2 diabetic rat aortae. Studies were performed in a normal control group (NC) (0.2 ml i.p. saline, n = 10), streptozotocin (STZ)/nicotinamide diabetic control group (DC) (a single dose of 80 mg/kg STZ i.p. injection 15 min after administration of 230 mg/kg nicotinamide i.p.), GLP-1 (GLPC) control group (1 µg/kg twice daily i.p. for 1 month, n = 10), Exendin-4 control group (EXC) (0.1 µg/kg twice daily i.p. for 1 month,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 106 publications
(66 reference statements)
2
32
0
1
Order By: Relevance
“…After 7 days, animals received vehicle or a single intraperitoneal injection of CCl 4 , 0.4 ml per 100 g body weight (50% mineral oil:CCl 4 ), which triggers cholangiocyte cell death by apoptosis 20. Subsequently, animals were treated with either (1) exendin-4 (0.1 μg/kg body weight twice a day, intraperitoneally, n = 8) or (2) control injections (n = 8) 9 21. Rats subjected to BDL, injected with vehicle and treated with control solution were used as internal controls (n = 4).…”
Section: Methodsmentioning
confidence: 99%
“…After 7 days, animals received vehicle or a single intraperitoneal injection of CCl 4 , 0.4 ml per 100 g body weight (50% mineral oil:CCl 4 ), which triggers cholangiocyte cell death by apoptosis 20. Subsequently, animals were treated with either (1) exendin-4 (0.1 μg/kg body weight twice a day, intraperitoneally, n = 8) or (2) control injections (n = 8) 9 21. Rats subjected to BDL, injected with vehicle and treated with control solution were used as internal controls (n = 4).…”
Section: Methodsmentioning
confidence: 99%
“…Although there is reason to question immunodetection of GLP-1R expression using antibody-based methodologies available prior to 2013 [55], there is considerable evidence that GLP-1R is functionally expressed in the endothelium, as activation with GLP-1 (7-36), GLP-1R agonists, or DPP-4 inhibitors results in phosphorylation of endothelial nitric oxide synthase (eNOS) at Ser1177, production of nitric oxide, and suppression of endothelin-1 expression [53, 5659]. Studies in isolated aorta [60, 61], pulmonary arteries [62], and rodent hearts [12, 16] also support that GLP-1 mediates vasodilation via an endothelial-dependent mechanism. Signaling pathways implicated in these endothelial effects of GLP-1 include AMPK [56] and cAMP/PKA-PI3K/Akt dependent activation of K ATP channels (Summarized in Figure 1) [51, 59, 61, 63].…”
Section: Glp-1 Effects On Tissue Perfusionmentioning
confidence: 99%
“…In a diabetic rat model it was shown that GLP-1 infusion nearly re-established normal vascular tone of aortic strips [9]. Moreover, in vitro studies revealed that DPP-4 is expressed in endothelial cells and that inhibition of DPP-4 reduced the microvascular tone through direct mediation of the NO system [10].…”
Section: Introductionmentioning
confidence: 99%